The Correlation between Self-Regulated Online Reading Habits and Writing Argumentative Essay Ability among EFL Students - Gunawan (Retain: Journal of Research in English Language Teaching, 2026)
In the digital age, students' online reading engagement is mediated by self-regulated learning. This study investigates the relationship between self-regulated online reading behavior and students’ ability to write argumentative essays in the context of English as a Foreign Language (EFL). This study employed a quantitative correlational design involving 42 undergraduate students from the English Education Department at Surabaya State University as participants. Two instruments were used: a self-learning questionnaire on online reading habits and a writing test based on Toulmin's Argumentation Model, which is a framework for analyzing and constructing arguments The descriptive statistical analysis using SPSS version 22 revealed mean scores of 4.3 for self-regulated online reading habits and 4.21 for argumentative writing ability. These results indicate that students demonstrated strong abilities in processing reading sources, utilizing information effectively, and expressing ideas in written form. In addition, Pearson correlation analysis revealed a correlation coefficient of 0.409, indicating a moderate relationship between online reading habits (X) and writing skills (Y). The Pearson Correlation value shows a positive relationship or correlation between variables. The significance level of p < 0.05 was used as the criterion to determine the presence of a statistically significant correlation. These findings highlight the potential of self-regulated online reading strategies to enhance students’ academic writing performance.